Pengaruh Lingkungan Keluarga Dan Disiplin Belajar Terhadap Motivasi Belajar Siswa Madrasah Tsanawiyah Nurul Cholil 3 Kelas IX Bangkalan Madura - Masduki Masduki; Didit Darmawan (Mathematics Education Study Program, 2025)
The success and failure of student learning are largely influenced by the students' own learning motivation. This motivation can be affected by family environment (external factors) and learning discipline (internal factors). This study aims to determine the extent to which the family environment and learning discipline influence the learning motivation of ninth-grade students at Madrasah Tsanawiyah Nurul Cholil 3 Bangkalan, Madura. The type of research used is quantitative with a correlational approach. The population in this study consists of all students at Madrasah Tsanawiyah Nurul Cholil 3 Bangkalan, Madura, totaling 102 students, with 35 ninth-grade students selected as respondents using a cluster sampling technique. This method involves dividing the entire population into clusters or groups, from which a random sample is taken, ultimately forming the final sample. The variables in this study include the independent variable (X1) family environment, independent variable (X2) learning discipline, and the dependent variable (Y) student learning motivation. Data were collected using questionnaires and documentation. The data analysis method employed is descriptive percentage analysis and multiple linear regression analysis. The data analysis results show that the family environment and learning discipline have a significant impact on student learning outcomes, with a p-value of 0.000, indicating p-value < α (0.05).Based on these findings, it can be concluded that both family environment and learning discipline, individually and simultaneously, have a very strong influence on students' learning motivation. Therefore, parents should actively demonstrate their support and express their expectations to their children or students, offering recognition and praise for their learning efforts. This will help maintain and even enhance the children's discipline and learning motivation